Examining the role of public relations departments in universities and their relationships with the graduates in Palestine - Almudallal, Mohammed W.; Bakri, Norhani (2017)
This paper aims to investigate the role of public relations departments in universities and how they deal with graduates.Universities in general have PR departments which are created to increase their missions and strengthen their visions.Frequently, the PR department is responsible of enhancing the objectives of the university to improve its image to publics.This study therefore investigates the extent of the PR role as a tool for facilitating the achievement of the objectives of universities. Data for the study was collected from a sample of one hundred and twenty (120) respondents sampled from graduates of the university.Which %78.3 are males and %21.7 are females from different districts in Gaza Strip in Palestine.Findings from the study showed that the administration of the PR department reinforces affiliation of graduates to their university. Furthermore, the PR department mainly participates in holding graduation ceremonies and in coordination with other departments in the university.The PR department continues with the graduates to have suitable jobs for them in the future.It also communicates with graduates through various means of social connectivity websites.